Association of Perfluoroalkyl Substances, Bone Mineral Density, and Osteoporosis in the U.S. Population in NHANES 2009-2010 - Khalil, Naila; Chen, Aimin; Lee, Miryoung; Czerwinski, Stefan A.; Ebert, James R.; DeWitt, Jamie C.; Kannan, Kurunthachalam (My University, 2015)
Background Perfluoroalkyl substances (PFASs), including perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorohexane sulfonic acid (PFHxS), and perfluorononanoic acid (PFNA), are detectable in the serum of 95% of the U.S. population. Objective Considering the role of PFASs as endocrine disruptors, we examined their relationships with bone health. Methods The association between serum PFAS concentration and bone mineral density at total femur (TFBMD), femoral neck (FNBMD), lumbar spine (LSBMD), and physician-diagnosed osteoporosis was assessed in 1,914 participants using data from the National Health and Nutritional Examination Survey 2009–2010. Results The mean age of the participants was 43 years. Men had higher serum PFAS concentrations than women (p < 0.001) except for PFNA. In both sexes, serum PFOS concentrations were inversely associated with FNBMD (p < 0.05). In women, significant negative associations were observed for natural log (ln)–transformed PFOS exposure with TFBMD and FNBMD, and for ln-transformed PFOA exposure with TFBMD (p < 0.05). In postmenopausal women, serum PFOS was negatively associated with TFBMD and FNBMD, and PFNA was negatively associated with TFBMD, FNBMD, and LSBMD (all p < 0.05). With one log unit increase in serum PFOA, PFHxS, and PFNA, osteoporosis prevalence in women increased as follows: [adjusted odds ratios (aORs)] 1.84 (95% CI: 1.17, 2.905), 1.64 (95% CI: 1.14, 2.38), and 1.45 (95% CI: 1.02, 2.05), respectively. In women, the prevalence of osteoporosis was significantly higher in the highest versus the lowest quartiles of PFOA, PFHxS, and PFNA, with aORs of 2.59 (95% CI: 1.01, 6.67), 13.20 (95% CI: 2.72, 64.15), and 3.23 (95% CI: 1.44, 7.21), respectively, based on 77 cases in the study sample. Conclusion In a representative sample of the U.S. adult population, serum PFAS concentrations were associated with lower bone mineral density, which varied according to the specific PFAS and bone site assessed. Most associations were limited to women. Osteoporosis in women was also associated with PFAS exposure, based on a small number of cases.